Teaching the Effects of Force at Grade Level VI : Textual Activities versus Hands-on Activities - Kishore, Lalit; Tamhane, Tushar (SCHOOL SCIENCE, 2013)
The effects of force form an important concept at the middle school level. In the NCERT syllabus for Class VI, the concept comes under the topic of “Motion, Force and Machines” (Lahiry et. al. 1987). After the idea of force has been introduced to the students, it is quite worthwhile to introduce the effects of force through some activities to give students the first-hand feel of the same. Though the NCERT book Science: A Textbook for Class VI has given some activities to introduce the concept but common experience of teachers indicates that the activities described in the textbook are not dramatic and challenging and children find them common place and dull. Therefore it was thought that some alternate activities in which more dramatisation, along with some hands-on aspect, connected with assembly and construction of the activities are there, should be developed.